2006
DOI: 10.1111/j.1440-1843.2006.00827.x
|View full text |Cite
|
Sign up to set email alerts
|

Emphysema detected by lung cancer screening with low‐dose spiral CT: Prevalence, and correlation with smoking habits and pulmonary function in Japanese male subjects

Abstract: A considerable percentage of the subjects with emphysema as detected by CT screening had GOLD stage 0. CT screening assists in detecting early-stage emphysema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 28 publications
3
54
1
Order By: Relevance
“…Approximately one-third of the study cohort had CT scan fi ndings of emphysema, a proportion similar to that found in other lung cancer screening studies from Spain 7 and Japan. 12 As mentioned previously, in one by the associations between CT scan evidence for emphysema, the diagnosis of lung cancer, and death from COPD and lung cancer. The current data also show that a considerable proportion of asymptomatic smokers have evidence of smoking status.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately one-third of the study cohort had CT scan fi ndings of emphysema, a proportion similar to that found in other lung cancer screening studies from Spain 7 and Japan. 12 As mentioned previously, in one by the associations between CT scan evidence for emphysema, the diagnosis of lung cancer, and death from COPD and lung cancer. The current data also show that a considerable proportion of asymptomatic smokers have evidence of smoking status.…”
Section: Resultsmentioning
confidence: 99%
“…Data on the epidemiology of emphysema in ''healthy'' smokers are forthcoming from populations screened by lung cancer [24][25][26]. Both prevalence and severity of emphysema on lowdose CT have already been shown to be greater in male than in female smokers [24,26].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that qualitative assessment is a valid and reliable tool for the characterization of emphysema on CT. 6 Furthermore, the prevalence of emphysema based on qualitative measurements in this study population is similar to what has been reported in other series of high-risk individuals. 29 Lastly, we lacked complete information about current smoking status of some study participants. Thus, we were not able to adjust for the potential influence of smoking status (current vs former) on the risk of lung cancer in the multivariate analyses.…”
Section: Discussionmentioning
confidence: 99%